Estudio en el control de calidad de los procesos del departamento de comunicación social de la Escuela Superior Militar Eloy Alfaro, durante el periodo diciembre 2012-abril 2013 - Riera Chamba, Patricia Isabel (2014)
This thesis refers to " STUDY ON QUALITY CONTROL PROCESSES SOCIAL COMMUNICATION DEPARTMENT OF HIGHER MILITARY SCHOOL " ELOY ALFARO " DURING DECEMBER 2012- APRIL 2013 " The objective was to : determine whether the processes running in the Department of Communication at the Military " Eloy Alfaro " College , develop optimally according to quality controls . The methodology and the technique used for the preparation of this research work was, " Description " , a survey of staff which includes the Department of Communication at the Military " Eloy Alfaro " In High School which was suggested to implement a tool facilitates control of the processes in the Department of Communication , and that globalization has allowed all institutions have a race against time to improve all quality systems either in the technological framework and human resource management . Application of the survey staff of the Department of Social Communication concludes that : 100% of staff surveyed indicated that if they would like a new tool that facilitates the control of processes in the Department of Social Communication is implemented. Proposal: Propose implementation of computer software ( GLPI ) by a utilitarian guide in the Department of Social Communication , establishing quality management processes that are strengthened and that , go with a schedule of training for staff in our department Military Communication " Eloy Alfaro " School . This software will positively improve all quality indicators that the institution has drawn within its mission.